Various Technical Parameters Influencing to Production of Polyscias Fruticosa Tea - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Polysicas fruticosa is available throughout Vietnam. This plant species contains large quantity of saponin. We have identified some basic chemical components of the leaf Polyscias fruticosa as moisture, ash and saponin content. On that basis, we chose the initial drying of the raw material with a vacuum drying method, the drying temperature of 50oC, for 6 hours to achieve a humidity of < 13% as required for medicinal herbs; The method of hot extraction in solvents is 70% ethanol with a solid/liquid ratio of 1/8, at a temperature of 70oC and extraction for a period of 1 hour limit affecting product quality. Examining the heavy metals and microbiological indicators of dissolved powders from Polyscias fruticosa, the product has produced standards for food safety as prescribed by the Vietnamese Ministry of Health.Keywords: Polyscias fruticosa, saponin, Drying, Extraction, Ethanol, Powder.